Can Productive Zakat, Entrepreneurial Experience, and Information Technology Drive MSME and SME Performance? A Case Study of BAZNAS Sleman Regency - Mohamad Salman Hidayat; Moh Shadam Taqiyyuddin Azka (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
This study investigates the impact of productive zakat, entrepreneurial experience, and information technology on the performance of Micro, Small, and Medium Enterprises (MSMEs) and Small and Medium Industries (SMIs). It focuses on 150 MSME and SMI actors funded by BAZNAS in Yogyakarta City and Sleman Regency, utilizing primary data collected via offline questionnaires. Multiple linear regression analysis, conducted using SPSS 27 and Microsoft Excel, reveals that productive zakat significantly enhances performance by increasing capital and providing sustainable support. Entrepreneurial experience also positively influences performance, offering practical skills and insights for overcoming business challenges. However, information technology shows no significant effect, attributed to low adoption and limited utilization. To bridge this gap, BAZNAS should implement targeted training on digital tools and e-commerce. The study highlights the need for integrated strategies combining financial, experiential, and technological support to drive sustainable growth among MSMEs and SMIs.